Mexico : The Strategy to Achieve Sustained Economic Growth - Loser, Claudio; Kalter, Eliot (Washington, D.C. : International Monetary Fund, 1992)
This paper explores the reasons behind the recent transformation and upturn of the Mexican economy. the changes are the result of the authorities' determination to stick with a difficult reform program since the early 1980s, supported by multilateral financial institutions, creditor countries, and commercial banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet